The impact of folding modes and deuteration on the atomic resolution structure of hen egg‐white lysozyme. Issue 12 (18th November 2021) - Ramos, Joao; Laux, Valerie; Haertlein, Michael; Forsyth, V. Trevor; Mossou, Estelle; Larsen, Sine; Langkilde, Annette E.
Abstract : A study of in vitro refolding and isotope effects on protein structure, activity and stability shows that different folding dynamics can lead to important changes in protein properties. Abstract : The biological function of a protein is intimately related to its structure and dynamics, which in turn are determined by the way in which it has been folded. In vitro refolding is commonly used for the recovery of recombinant proteins that are expressed in the form of inclusion bodies and is of central interest in terms of the folding pathways that occur in vivo . Here, biophysical data are reported for in vitro ‐refolded hydrogenated hen egg‐white lysozyme, in combination with atomic resolution X‐ray diffraction analyses, which allowed detailed comparisons with native hydrogenated and refolded perdeuterated lysozyme. Distinct folding modes are observed for the hydrogenated and perdeuterated refolded variants, which are determined by conformational changes to the backbone structure of the Lys97–Gly104 flexible loop. Surprisingly, the structure of the refolded perdeuterated protein is closer to that of native lysozyme than that of the refolded hydrogenated protein. These structural differences suggest that the observed decreases in thermal stability and enzymatic activity in the refolded perdeuterated and hydrogenated proteins are consequences of the macromolecular deuteration effect and of distinct folding dynamics, respectively. These results are discussed in the context of both in vitro and in vivo folding, as well as of lysozyme amyloidogenesis.